Physical Quality of Sago Waste Silage with Different Concentrations of Cattle’s Rumen Liquid - Wildan Hanifah; Dewi Febrina; Elviriadi Elviriadi; Putri Zulia Jati; Abdul Fatah (Jurnal Peternakan, 2023)
Sago waste can be used as a substitute for carbohydrate feed sources but is constrained by the high content of crude fiber and low crude protein. Pretreatment with fermentation treatment is expected to improve the physical quality of silage. This study aimed to determine the addition of different concentrations of cattle’s rumen liquid on the physical quality and pH of sago waste silage. The research design used a Completely Randomized Design with 4 treatments and 4 replications. Each treatment included: T0 = sago waste + 0% cattle’s rumen liquid; T1 = sago waste + 2% cattle’s rumen liquid; T2 = sago waste + 4% cattle’s rumen liquid; T3 = sago waste + 6% cattle’s rumen liquid. The result showed the physical quality (color, aroma, and texture) was very significant (P<0.01) influenced by the addition of different concentrations of cattle’s rumen liquid, and the pH of silage was not significant (P>0.05) effect. Sago waste silage which was the addition of 6% cattle’s rumen liquid gave the best physical quality, judged by light brown color (3.518 ± 0.02), the distinctive aroma of silage (3.61 ± 0.04), dense texture, crumbly, and not slimy (3.58 ± 0.02), as well acidic pH (4.40 ± 0.18).